The Hydraenidae of Cuba (Insecta: Coleoptera) II: Morphology of preimaginal stages of six species and notes on their biology - Deler-Hernández, Albert; Delgado, Juan A. (Zootaxa, 2017)
Preimaginal stages of the six species of Hydraenidae presently known from Cuba were obtained by rearing adults in the laboratory. Eggs of Hydraena perkinsi Spangler, 1980, H. decui Spangler, 1980 and H. franklyni Deler-Hernández & Delgado, 2012 are described and illustrated for the first time. The first instar larva of Gymnochthebius fossatus (LeConte, 1855) is redescribed, adding some new remarkable morphological characters including what could be the first abdominal egg-burster reported for this family. All larval instars of H. perkinsi, H. guadelupensis Orchymont, 1923 and Ochthebius attritus LeConte, 1878 are described and illustrated for the first time, with a special emphasis on their chaetotaxy. The second instar larva of G. fossatus along with first and third instar larvae of H. decui and H. franklyni are also studied for the first time. The pupal morphology and vestiture of a species belonging to the genus Hydraena are described for the first time, based on the pupa of H. perkinsi. Biological notes for several preimaginal stages of the studied species are also given.